2011
DOI: 10.1068/p6524
|View full text |Cite
|
Sign up to set email alerts
|

Change Detection in Complex Scenes: Hemispheric Contribution and the Role of Perceptual and Semantic Factors

Abstract: The perceptual salience and semantic relevance of objects for the meaning of a scene were evaluated with multiple criteria and then manipulated in a change-detection experiment that used an original combination of one-shot and tachistoscopic divided-visual-field paradigms to study behavioural hemispheric asymmetry. Coloured drawings that depicted meaningful situations were presented centrally and very briefly (120 ms) and only the changes were lateralised by adding an object in the right or in the left visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 95 publications
5
11
0
2
Order By: Relevance
“…First, they indicate that previous controversial evidence about an inconsistency advantage for selection prioritisation during viewing (e.g., Bonitz & Gordon, 2008;Brockmole & Henderson, 2008;Cornelissen & Võ, 2017;Hollingworth & Henderson, 2003;Loftus & Mackworth, 1978;Stirk & Underwood, 2007;Underwood et al, 2007Underwood et al, , 2008 may have arisen from a bias in informativeness per se, due to comparisons with poorly informative objects. Second, they corroborate previous research, carried out in the change detection domain, which considered consistent/diagnostic and consistent/low informative objects and showed that informativeness in terms of diagnosticity for scene leads to preferential selection Pringle et al, 2001;Rensink et al, 1997Rensink et al, , 2000Spotorno & Faure, 2011). We reinforce this earlier claim by demonstrating that diagnosticity prioritisation holds true even when removing the imbalance in informativeness between the compared objects.…”
Section: Semantic and Perceptual Prioritisation In Scene Processingsupporting
confidence: 90%
“…First, they indicate that previous controversial evidence about an inconsistency advantage for selection prioritisation during viewing (e.g., Bonitz & Gordon, 2008;Brockmole & Henderson, 2008;Cornelissen & Võ, 2017;Hollingworth & Henderson, 2003;Loftus & Mackworth, 1978;Stirk & Underwood, 2007;Underwood et al, 2007Underwood et al, , 2008 may have arisen from a bias in informativeness per se, due to comparisons with poorly informative objects. Second, they corroborate previous research, carried out in the change detection domain, which considered consistent/diagnostic and consistent/low informative objects and showed that informativeness in terms of diagnosticity for scene leads to preferential selection Pringle et al, 2001;Rensink et al, 1997Rensink et al, , 2000Spotorno & Faure, 2011). We reinforce this earlier claim by demonstrating that diagnosticity prioritisation holds true even when removing the imbalance in informativeness between the compared objects.…”
Section: Semantic and Perceptual Prioritisation In Scene Processingsupporting
confidence: 90%
“…This was observed in our data. In agreement with this view, changes are detected faster in the left hemifield in the change-blindness paradigm (Lyilikci, Becker, Güntürkün & Amado, 2010;Spotorno & Faure, 2011). This has been shown in detection experiments in which scenes were flickered and has not yet been investigated in saccade-contingent paradigms.…”
Section: Discussionsupporting
confidence: 75%
“…On the behavioral level, our findings are in line with a right-hemispheric specialization for the maintenance of spatial information, and a left-hemispheric specialization for the maintenance of verbal information (Machizawa et al, 2012;Reuter-Lorenz et al, 2000;Smith & Jonides, 1998;Spotorno & Faure, 2011;Thomason et al, 2008). In the spatial task, performance was higher for stimuli presented in the left hemifield, whereas in the verbal task performance was higher for stimuli presented to the right hemifield.…”
Section: Discussionsupporting
confidence: 85%